ECOSTORIES IN VISUAL COMMUNICATION DESIGN FOR ENVIRONMENTAL CAMPAIGNS ON THE @GREENPEACEID ACCOUNT - Made Sani Damayanthi Muliawan; Wayan Angga Kesuma Muliawan (Universitas Warmadewa, 2026)
This study aims to analyze how the microplastic campaign on the @greenpeaceid account builds an ecological narrative through a combination of language and visual communication design. The data sources are campaign materials, including text on posters and captions. The data used is qualitative data in the form of linguistic and visual elements. The method used is descriptive qualitative with two analytical frameworks: Arran Stibbe's ecolinguistics and visual communication theory, including Kress and van Leeuwen's visual grammar. Ecolinguistics analysis focuses on identity stories, framing, and erasure, while visual analysis covers visual hierarchy, AIDA persuasion structure, color selection, and layout. The results show that the campaign constructs identity stories that position the public as victims of systemic microplastic exposure, while industry and policymakers are framed as the main actors responsible for solutions. Visually, the campaign utilizes dark and earth tones, bold typography, and hierarchical composition to emphasize the immediacy of the threat and the urgency of action. The integration of linguistic and visual dimensions produces an ecological narrative that rejects the individualization of environmental blame and encourages collective action based on regulation.